Water blocking damage in hydraulically fractured tight sand gas reservoirs: An example from Perth Basin, Western Australia - Bahrami, Hassan; Rezaee, Reza; Clennell, B. (Elsevier BV, 2012)
Tight gas reservoirs normally have production problems due to very low matrix permeability and different damage mechanisms during drilling, completion and stimulation operations. Therefore they may not produce gas at commercial rates without production optimization and advanced completion techniques. Tight formations have small pore throat size with significant capillary pressure energy suction that imbibes and holds liquid in the capillary pores. Leak-off of liquid from the wellbore into the formation may damage near wellbore permeability due to water blocking damage and clay swelling, and it can significantly reduce well productivity even in hydraulically fractured tight gas reservoirs. This study presents evaluation of damage mechanisms associated with water invasion and phase trapping in tight gas reservoirs. Single well reservoir simulation is performed based on typical West Australian tight gas formation data, in order to understand how water invasion into the formation affects well production performance in both non-fractured and hydraulically fractured tight gas reservoirs. A field example of hydraulic fracturing in a West Australian tight gas reservoir is shown and the results are analyzed in order to show importance of damage control in hydraulic fracturing stimulation of low permeability sand formations. The study results highlight that water blacking can be a major damage mechanism in tight gas reservoirs. In water sensitive tight sand formations, damage control is essential and the well productivity improvement may not be achieved in the case of excessive water leak-off into formation during hydraulic fracturing operations.